Antimicrobial and bacteriostatic activity of surfactants against B. subtilis for microbial cleaner formulation - Vehapi, Meyrem; Ozcimen, Didem (SPRINGER HEIDELBERG, 2021)
Cleaning products containing live bacteria that form spores of Bacillus spp. as active substances are becoming increasingly common in probiotic cleaner formulation. The quality of cleaning performance for the production of probiotic cleaners does not only depend on the potential of the bacterial strains used, but also on the chemical components of the formulations. In this study, the surfactants and other additives were investigated as biocidal or bacteriostatic against B. subtilis, and the viability of B. subtilis was examined at different pH ranges for microbial cleaner formulation. As a result, it was discovered that the B. subtilis, which can be used in the microbial cleaner formulation, shows higher growth and viability at the neutral pH, and it passes into the death phase at pH 3. According to antagonistic activity results, the Gram-positive S. aureus and K. pneumoniae were the most sensitive bacteria while B. cereus was the most resistant bacteria. The anionic surfactants such as linear alkylbenzene sulfonic acid and sodium lauryl ether sulfate act as bacteriostatic on Bacillus spp. and do not cause cell death. In the view of these results, the usage of appropriate bacterial cultures and the correct stabilization of the formulations are also critical elements in the development of microbial cleaner formulations.
Keywords: B; subtilis; Probiotics; Microbial based cleaning; Surfactants; Bacteriostatic activity; Antagonistic activity; Microbiology